Ground servitude of transmission as a constitutional problem - Chęciński, Remigiusz; Marzec, Tomasz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The aim of the study is to analyse the institution of civil law – transmission servitude and its understanding by the Highest Court of the Republic of Poland, shown in the jurisdiction of that Court. The authors study each judgment of the Highest Court, which present the Court’s understanding of that institution. The rulings are subject to constitutional control. The courts of law in Poland issued a couple of legal questions to the Polish Constitutional Tribunal, in which the courts inquired if this understanding of transmission servitude is compatible with the constitution. The authors describe the consequences of the Tribunal’s in the context of the Constitution of Republic of Poland.